Introduction: Migration and Unequal Positions in a Transnational Perspective - Faist, Thomas (2021)
How does spatial mobility influence social mobility and vice versa? Often, the ‘objective’ structural positions on the one hand, and the ‘subjective’ definition of social positions on the other hand, are not considered together. Yet this is necessary in order to gauge the consequences of mobility trajectories reaching across borders. This framing editorial asks how we can study the interplay of perceptions of one’s own social position and one’s objective social position to better understand how spatial mobility influences social mobility and vice versa. In short, this means an exploration of the nexus of spatial mobility and social mobility. Exploring that nexus requires attention to objective social positions, subjective social positioning strategies, transnational approaches to the study of social positions and self-positioning, and social boundary theory. Overall, the complexity of the nexus between social and spatial mobilities calls for a multifaceted research approach that covers various levels of analysis. Some of the contributions feature a mixed-methods approach that allows drawing a multifaceted picture of the interrelation between the perceptions of social positions and their structural features.